Tendency and prospects assessment for the development of “green energy” in the conditions of sustainable development - Pochtovyuk, Andrew; Pryakhina, Katerina; Bilyk, Maryna (Research Papers of Wrocław University of Economics, 2018)
The article formulates the scientific research: consideration of the prospects for development of the renewable energy in the world and in the European Union; the analysis and the condition of the energy strategy of Ukraine and the two projects of a new document – Energy Strategy of Ukraine till 2035; and the exploration of the strategy development prospects of “green energy” in Ukraine. The aim of the research is to evaluate the prospects of the development of “green energy” in Ukraine by means of analysis and synthesis of the power strategies of the countries of the world, Europe, as well as Ukraine. Ukraine has committed itself to reduce greenhouse gas emissions, having signed Paris agreement on climate change on April 22, 2016. It has a direct impact on the development of energy sector and affects the strategy to expand the use of renewable energy
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 502, s. 104-112
Keywords: renewable energy sources; energy strategy; odnawialne źródła energii; strategia energetyczna